A Catalogue of Indian Stoneflies (Insecta: Plecoptera) - Chandra, Kailash; Gupta, Devanshu; Ahmed, Ishtiaq (Zootaxa, 2019)
This catalogue lists 146 valid species included in 27 genera and 8 families of the order Plecoptera (Insecta) recorded from India. We record the nomenclatural changes of the species names, type localities, type depositories, and distribution. The Himalayan Region supports the greatest diversity (87 species), followed by the Northeast Region (51 species), Deccan Peninsula (18 species), Western Ghats (11 species), and Trans Himalaya (6 species). The Nemouridae (69 species, 7 genera) and Perlidae (49 species, 9 genera) represent nearly 80% of the species known from India. Approximately, 90 species are endemic to India.